Arusak - Atoeva, Robiya (Tajikistan : Kinoservice Ltd., 2002)
The documentary represents the author’s observations on the way of life experienced by contemporary Tajik girls and women. In times that are hard for themselves, for their families and for society, they find the strength to affirm their human dignity, to reflect on life, the lot of women and love. And there is not a grain of falsity in their stories, recollections and confessions.
Duration: 00:30:00
Keywords: Documentary films